2022
DOI: 10.1007/s00101-022-01192-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with divided anesthesia care

Abstract: Background Up to now, no prospective cohort study using a validated questionnaire has assessed patients’ expectation and perception of divided anesthesia care and its influence on patient satisfaction. Objective We assessed patient satisfaction with divided anesthesia care in a district general hospital in Switzerland. We hypothesized that patient expectations, combined with their perceptions of the (un)importance of continuous anesthesia care would influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This study was based on a secondary analysis of data from a prospective cohort study on patient satisfaction with divided anaesthesia care. This study was approved by the Medical Ethics Committee of St. Gallen, Switzerland (Business Administration System for Ethics Committees 2017–00,090; Registry of all Projects in Switzerland—RAPS—registration number: 2017-00090) 7 . The requirement for informed consent for secondary analysis was waived by the Medical Ethics Committee of St. Gallen, Switzerland.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was based on a secondary analysis of data from a prospective cohort study on patient satisfaction with divided anaesthesia care. This study was approved by the Medical Ethics Committee of St. Gallen, Switzerland (Business Administration System for Ethics Committees 2017–00,090; Registry of all Projects in Switzerland—RAPS—registration number: 2017-00090) 7 . The requirement for informed consent for secondary analysis was waived by the Medical Ethics Committee of St. Gallen, Switzerland.…”
Section: Methodsmentioning
confidence: 99%
“…The 55-item patient satisfaction questionnaire used in our study was psychometrically developed according to a stepwise protocol and retested several times for construct validity and reliability 5 , 7 , 10 , 11 . Three non-quality-of-care-related questions within the questionnaire specifically addressed anaesthesia-related anxiety (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the sub-dimension "continuity of care", modern anaesthesia services are limited in the scope of actions mostly by the development towards preoperative anaesthesia wards, thus divided care 7 . "Respect and trust" in the patient-anaesthetist relationship highly depends on non-technical skills of the treating physician [36][37][38][39] , which gained attention for resident and anaesthesia nurse training as well as continuing education only in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The 55-items patient satisfaction questionnaire used in our study has been psychometrically developed and re-validated several times 1,7,10,11 . Three non-quality of care related questions speci cally address anaesthesia-related anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, in some cultures, continuity of care is still important to patients [23], even though divided care has already become the new standard [51]. In a recent study, Koster et al [52] found that despite receiving comprehensive preoperative information about divided anaesthesia care, 40% of patients still considered continuity of care by the same anaesthetist important. The mean total dissatisfaction score of the group who considered continuity of care important but did not receive it (110 patients out of 484) was 25% (95% confidence interval, 21.8–28.1) compared with 12% in the group of patients (222 out of 484) who did not emphasize the importance of continuity of care (95% confidence interval 10.7–13.4).…”
Section: The Engaged Physicianmentioning
confidence: 99%